Some aspects of structure formation in sintering process between cuprum fibers and Zn - V. G. Shcherbakou (Литьë и металлургия, 2019)
The article reveals some aspects of structure formation between cuprum fibers and Zn in fluidized powder mixture. It was established that diffusion saturation of cuprum fibers with Zn leads to formation of diffusion layer with decreased melting temperature. The presence of high concentrated Zn zones on the top of the each separate fiber results in improved compactability and sintering temperature in that of high importance in production of porous filter materials.